Direct measurement of aerosol glass fiber alignment in a DC electric field. Issue 2 (1st February 2018) - Ku, Bon Ki; Deye, Gregory; Turkevich, Leonid A.
ABSTRACT: We report non-conducting aerosol fiber (i.e., glass fiber) alignment in a DC electric field. Direct observation of fiber orientation state is demonstrated and quantitative analysis of fiber alignment is made using phase contrast microscopy in four different conditions: (i) dry air and naturally charged fibers, (ii) humid and naturally charged, (iii) humid and neutralized (Boltzmann charge distribution), and (iv) humid and neutralized with an electrostatic precipitator upstream electrodes (i.e., non-charged). The glass fiber aerosols generated by a vortex shaking method were conditioned using a Po-210 neutralizer or humidifier and were provided into a test unit where cylindrical or parallel plate electrodes are used and high voltage is applied to them. Fibers were collected on a filter immediately downstream from the electrodes and their images were taken through an optical microscope to visualize the fiber orientation and measure the alignment angles and lengths of the fibers. The results showed that under all four conditions tested, airborne glass fibers could be aligned to the electric field with different alignment quality, indicating that the glass fibers can be polarized in a steady electric field. In humid air, the fiber alignment along the field direction was observed to be much better and the number of uniform background particles (i.e., randomly oriented fibers) in angular distributions is smaller than that in dry air. Also, it was found that charged fibers in humid air could be better aligned with negligible uniform background than neutralized and non-charged fibers. Possible mechanisms about humidity and charge effects on enhanced fiber alignment are discussed to support the observations. The results indicate that the enhancement of alignment in an electric field would be possible in humid air for other non-conducting fibrous particles having surface chemistry similar to glass fibers.